IMPLEMENTASI SIG UNTUK PEMETAAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) PRODUK KHAS KOTA PALEMBANG - Eka Puji Agustini (Jurnal Ilmiah Matrik, 2020)
Geographically the area of Palembang City is 400.61 km2 which is divided into 16 subdistricts and 107 villages and has a sizeable population. The Office of Cooperatives, Small and Medium Enterprises in Trade and Industry of Palembang City as an office directly related UMKM has mapped UMKM in Palembang City but this mapping is still limited to reporting, and is not yet widely accessible to the public. Therefore this study aims to map UMKM geographically and publicly accessible. This mapping will be built using Arcgis technology and Geographic Information System which is an application of earth data processing by looking at spatial data and attribute data. The results of this study are in the form of a GIS application that maps the UMKM of Palembang City.